Farmers’ preferences for sustainable intensification attributes in sorghum-based cropping systems: Evidence from Mali - Badolo, F.; Kotu, Bekele Hundie; Oyinbo, O.; Sanogo, Karamoko; Zemadim, Birhanu (Cambridge University Press, 2022)
Sorghum plays a crucial role in the rural economy and nutrition of rural households in Mali. Yet the productivity of this crop is constrained by limited adoption of agricultural intensification technologies, which could be partly because technology development does not properly consider farmers' preferences. This study with smallholder farmers in southern Mali aimed to assess farmers' preferences for different attributes of sorghum technologies through the lens of sustainable intensification. The study used a discrete choice experiment, a method which involves asking individuals to state their preference over hypothetical alternative scenarios, goods or services. We considered six attributes corresponding to different domains of sustainable intensification: grain yield, risk of yield loss, soil fertility, nutrition, labor requirement and fodder yield. We analyzed the data using the mixed logit model, while considering the multinomial logit model as a robustness check. The findings revealed that smallholder farmers are strongly interested in transitioning from their existing sorghum-based cropping systems to those that closely align with these domains of sustainable intensification. However, there were diverse preferences among all the smallholder farmers studied, and between distinct sub-groups of smallholder farmers characterized by their social networks and agroecological zones, which yield relevant policy implications. Overall, these results support the growing research and development prioritization and policy interests toward scaling sustainable intensification among farmers, with a particular focus on human nutrition.